Regional sentiment indexes and their association with timely indicators of economic activity in Mexico, 2016-2021 - Torre, Leonardo E.; González, Eva E.; Casillas, Luis R.; Alvarado, Jorge A. (Estudios Económicos de El Colegio de México, 2024)
We estimate sentiment indexes at the regional and national level using text data obtained from the Programa Trimestral de Entrevistas a Directivos del Banco de México, used to elaborate the Report on the Regional Economies regarding the factors that the interviewed consider affected, affect, or could affect economic activity in their sector or state. Using text data from quarterly interviews performed from January 2016 to January 2021, we associate these indexes with different indicators of regional and national economic activity published by INEGI. The estimates indicate positive and statistically significant correlations among the sentiment indexes and some economic activity indicators. Since the sentiment indexes can be estimated relatively faster than most of the traditional economic indicators analyzed, this paper outlines the relevance of the text data contained in the Programa Trimestral de Entrevistas a Directivos to supplement the information obtained from traditional indicators.